A CASE REPORT AND ROLE OF INTRAVENOUS IMMUNOGLOBULIN IN THE TREATMENT OF IMMUNE - MEDIATED NECROTIZING MYOSITIS - Nguyen Manh Linh,; Vu Thu Trang,; Vu Thi Mai Huyen,; Tran Le Linh Trang,; Nguyen Thi Phuong Nhung,; Tran Thi Mai,; Nguyen Lan Anh, (Tạp chí Y học Quân sự, 2026)
Objective: To report a rare case of idiopathic autoimmune myopathy that was successfully managed with intravenous immunoglobulin (IVIG) therapy. Methods: We described the clinical course, diagnostic workup, and therapeutic response of a patient definitively diagnosed with IMNM at the 108 Military Central Hospital. Results: A 62-year-old male presented with symmetrical proximal muscle weakness and markedly elevated creatine kinase (CK) levels (> 9,000 U/L). Serological testing was positive for anti-signal recognition particle (anti-SRP) antibodies, and muscle biopsy confirmed myofibre necrosis consistent with IMNM. Initially, the patient was treated with high-dose corticosteroids combined with mycophenolate mofetil, which resulted in poor response and progressive worsening of muscle weakness. Subsequent adjunctive therapy with IVIG (2 g/kg body weight was administered over 5 days, repeated after one month), along with optimized immunosuppression resulted in significant clinical improvement in muscle strength, restored mobility, CK levels and no significant adverse effects were observed during the treatment period. Conclusion: Intravenous immunoglobulin is an effective and well-tolerated therapeutic intervention for immune-mediated necrotizing myopathy, particularly in cases refractory to standard treatment.